Penerapan Media Amazing Topeng Malang untuk Meningkatkan Kemampuan Literasi dan Keterampilan Berpikir Kreatif dalam Pembelajaran Tematik Kelas IV SDN 2 Girimoyo, Malang - Rizqoh, Aini (Jurnal Didaktika Pendidikan Dasar, 2019)
The result of the initial thoughts on fourth-grade students of SDN 2 Girimoyo showed that literacy and learning of students can be improved through learning that integrates the Amazing Topeng Malang Media based on Local Wisdom as a source of learning. The objective of this study was to improve the literacy skills and creative thinking skills of students in learning by using the Amazing Topeng Malang Media. The research method used in Classroom action Research consists of planning, implementation, observation, and reflection. The result showed an increase in the average literacy skill of students = 69.00 with sufficient category in the first cycle was improve to = 82.00 with a good category in the second cycle. The average creative thinking skills of the students were improved to = 72.00 with sufficient category in the first cycle, and their creative thinking skills were improved to = 84.00 in the second cycle with the good category.